Prevention Techniques for Sybil Attack - Garg, Roopali; Sharma, Himika (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Mobile ad-hoc network is a self-governing network, consists of group of nodes that communicates with each other through wireless links. As it is a wireless network, so it is subjected to various attacks. There is one attack which is very dangerous called Sybil attack. In Sybil attack, attackers or malicious nodes uses multiple identities to disrupt the communication between the nodes by capturing necessary and important information and creating misunderstandings between the nodes. In this paper some measures are described to prevent Sybil attack.